IMPLEMENTASI KEBIJAKAN SMART GOVERNMENT DALAM RANGKA MEWUJUDKAN SMART CITY DI KOTA BANDUNG - Annisa Rahmadanita; Eko Budi Santoso; Sadu Wasistiono (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2018)
The application of smart city (especially in the aspect of smart government) in the city of Bandung is still focused on technology development, and seems to ignore the human and institutional dimensions. This study aims to describe and analyze the implementation of smart government policies in order to realize a smart city in the city of Bandung. The researcher used the theory presented by Grindle as a guide related to policy implementation. The researcher used a qualitative method with a descriptive approach. In collecting data, researchers conducted interviews with 37 informants, made observations with the participant as observer method, and collected documents about the implementation of smart government policies in order to realize smart cities. The results showed that (1) implementation of smart government policies in order to realize smart cities in the city of Bandung in general has a positive impact on target groups (target groups). Context of implementation (context of implementation) shows a condition that is not good while Content of policy shows good conditions. In this study the content of policy factor has more influence on outcomes / outcomes than factors of context of implementation. Because the implementation of the smart government policy in the city of Bandung is more influenced by content of policy than context of implementation, the researchers suggested to the Bandung City Government to maximize various conditions in the Content of Policy in order to improve the outcomes of implementing smart government policies that have been implemented.Keywords: Policy Implementation, Smart Government, Smart City